Protective Effects of Gallic Acid against Streptozotocin-induced Oxidative Damage in Rat Striatum - Naghizadeh, B.; Mansouri, M. T. (Drug Research, 2015)
The present study aimed to investigate the protective effects of gallic acid (GA) against ICV STZ-induced oxidative damage in the rat striatum. Animals were randomly divided into 4 groups (8 each). Group 1 (Sham), were injected ICV on day 1 and 3 with artificial CSF and treated with normal saline (2 ml/kg, p.o.). Group 2 (sham+GA), were injected ICV on day 1 and 3 with artificial CSF and treated with GA (30 mg/kg, p.o.) for 26 days. Group 3 (lesion) were injected with ICV-STZ (3 mg/kg bilaterally, on day 1 and 3) and received normal saline (2 ml/kg, p.o.) as vehicle. Group 4 (lesion+GA), were injected with ICV-STZ (3 mg/kg bilaterally, on day 1 and 3) and treated with gallic acid (30 mg/kg, p.o.) once daily for 26 days starting 5 days before the first injection of ICV STZ. The homogenized striatum was used for measuring thiobarbituric acid reactive species (TBARS) and total thiol contents, glutathione peroxidase (GPx), catalase (CAT), and superoxide dismutase (SOD) activities. The results showed that ICV STZ-injection increased the level of TBARS (+69.3%) and decreased total thiol concentration (−48.8%), GPx (−47.3%), CAT (−47.1%) and SOD (−30.7%) activities. In contrast, chronic administration of GA significantly prevented the biochemical alterations in the ICV-STZ rats. These findings highlight the beneficial role of GA via enhancement of cerebral antioxidant defense system.
Keywords: gallic acid (GA); streptozotocin (STZ); oxidative stress; striatum